Characterization and differential expression of microRNA in the freshwater shrimp (Neocaridina heteropoda) with different body length. Issue 1 (2nd January 2020) - Li, Ran; Wang, Xin; Meng, Qinghao; Ren, Liqi; Weng, Jieyang; Wang, Shen; Sun, Jinsheng
ABSTRACT: MicroRNAs (miRNAs) are a class of small non-coding RNAs which promote mRNA degradation and inhibit mRNA translation. Through post-transcriptional regulation, microRNAs (miRNAs) play a significant role in regulating growth, development, metabolic, and reproductive processes. However, current knowledge on miRNAs in crustaceans is limited. In this study, we explored the potential roles of miRNAs in abdominal muscle of Neocaridina heteropoda of different body length. We constructed two small RNA libraries from muscle samples, and 26 novel miRNAs were identified. Among these novel miRNAs, 13 were found significantly differentially expressed. Specifically, 10 miRNAs were significantly up-regulated and 3 miRNAs were down-regulated in small shrimps compared with large ones. Furthermore, bioinformatics analysis revealed that miR-26 was associated with a large number of differentially expressed genes, including glucose transporter 1 (Glut1), phosphoenolpyruvate carboxykinase (Pepck), and phosphofructokinase (Pfk), related to glycolysis and gluconeogenesis pathways. Besides, luciferase activity assay verified that Pepck was a direct target gene of the novel miR-26. The results imply potential growth regulatory roles for miRNAs and provide a valuable resource for further investigation of the miRNA mechanisms controlling muscle growth in N. heteropoda and other crustaceans. Abbreviations: Ago: argonaute; ANOVA: one-way analysis of variance; CRISPR: clustered regularly interspaced short palindromic repeats; DEGs: differentially expressed genes; DMEM: Dulbecco's Modified Eagle Medium; Glut1: glucose transporter 1; GO: Gene Ontology; KEGG: Kyoto Encyclopedia of Genes and Genomes; miRNA: microRNA; Pepck: phosphoenolpyruvate carboxykinase; PPIs: predict protein-protein interactions; Pfk: phosphofructokinase; RISC: RNA-induced silencing complex; siRNAs: small interfering RNAs; sRNA: small RNA; dsDNA: double-stranded DNA; qPCR: quantitative PCR